ETIKA, HAK, DAN DISIPLIN KERJA SDM PENDIDIKAN ISLAM: ANALISIS MANAJEMEN SDM BERBASIS NILAI-NILAI ISLAMI - Gusti Arizona, Indriani; Hamdi Abdul Karim (Pendidikan Dasar dan Manajemen Pendidikan, 2025)
This article aims to analyze the application of ethics, rights, and work discipline in human resource management in Islamic educational institutions. Human resources in the context of Islamic education are not only oriented towards intellectual and professional abilities, but also towards the formation of moral integrity, good character, and spiritual responsibility for the tasks undertaken. This study uses a descriptive qualitative approach through a literature review sourced from scientific journal and modern literature relevant to Islamic education management. The results show that the application of Islamic work ethics based on the values of trust, honesty, and justice can foster a harmonious, fair, and productive work environment. In addition, respect for the rights of educators and the establishment of a culture of continuous discipline are key to increasing professionalism and work loyalty. Thus, Islamic value-based HR management is not only oriented towards organizational efficiency, but also towards spiritual development and work welfare that is considered worship.